THE INFLUENCE OF CONDITIONS OF WORK ON PROFESSIONAL DISEASE INCIDENCE OF FOUNDERS - A. M. Lazarenkov; S. A. Horeva; V. V. Melnichenko; T. A. Tavgenj; I. V. Karpenko (Литьë и металлургия, 2005)
Conditions of work of workers in casting houses are examined. The influence of conditions of work on professional disease incidence of founders is shown.